Studi Kasus Pemodelan Vacuum Consolidation dan Prefabricated Vertical Drain - Cheryl, Monica Frances; Lim, Aswin (Universitas Ibn Khaldun, 2024)
Soft soil is soil with the potential for large consolidation settlements over a long period of time. Soft soil often causes problems for the structures above it due to the relatively low bearing capacity of the subgrade and long-lasting large soil compression. To accelerate the consolidation reduction that occurs, one of the latest steps for soil improvement is the vacuum consolidation method with a combination of prefabricated vertical drain (PVD). This method involves installing a vertical drain into soft soil where a vacuum pump will suck water and air in the soil which has been wrapped in airtight material on top. The vacuum process and application of vertical drain will cause a decrease in consolidation in the soil to occur more quickly. Initial loading with vertical drainage is carried out to induce most of the settlement of the underlying soil layer. The aim of this research is to model the soil improvement process with vacuum and PVD using the 2-dimensional finite element method. The study was carried out by carrying out reverse analysis, based on soil parameter data in North Jakarta which was adjusted to the decline curve over time in the field. Based on the analysis, the results obtained show that with the presence of PVD, the soil permeability in the horizontal direction of the model will increase so that the dissipation of pore water pressure will be faster. Plaxis modeling curves for reduction over time and pore water pressure over time have similar results to measurements in the field.